Penggunaan Kertas Pelapis Berlengkuas Sebagai Penghambat Cemaran Kapang pada Wingko - Atika Silvia Melyawati; Choirul Amri; Lilik Hendrarini (Sanitasi: Jurnal Kesehatan Lingkungan, 2020)
Food security is an effort needed to prevent food from possible biological, chemical or physicalcontamination that can endanger human health. Wingko is a semi-wet food that can be easilyovergrown with mold. Wingko production activities are closely related to the use of packagingpaper and the type of coating paper. One natural ingredients containing essential oils, flavonoids,and tannins as antimicrobials are galangal. The aim of the study was to know the concentrationvariation of galangal coated paper to inhibit of mold contamination on wingko. The studywas an experiment with post test only control group design. The data collection techniqueswas visual observation and using a checklist. The observation was carried out on wingko afterhave been exposed to galangal coated paper during the end of the shelf life or the appearanceof mold. The observation of the mold was on top, bottom, right and left sides of the wingko surface.The results showed that among the 3 variations of treatment (30%, 40%, 50%) and thecontrol, the mean of the shelf life of Wingko after intervention, were 5; 5; 5,3; and 4.1 days, respectively.Based on data analysis, it can be concluded that the addition of galangal liquid with50% concentration to coateing paper is the best variation of for inhibiting mold contamination onwingko and is able to extend the shelf life of wingko.